An atmospheric impact assessment of water-based hydrogen production methods: Sustainability evaluation - Ayşegül Yağmur Gören (MANAS: Journal of Engineering)
Population growth and urbanization have significantly affected the energy demand and environmental contaminant levels worldwide. Currently, global warming with greenhouse gas emissions, air pollution, acid rain, environmental degradation, and depletion of energy resources are all consequences of utilizing fossil fuel-powered energy infrastructure. Hence, renewable energy-powered alternative energy resources must be considered to minimize atmospheric emissions and environmental contaminants. Hydrogen (H2) has become a viable fuel to satisfy energy needs, and in recent years, there has been a lot of interest in green H2 production, particularly using electrolysis processes that produce no emissions. In this regard, this paper utilized the atmospheric emission assessment software to evaluate atmospheric contaminants from the alkaline electrolysis (AE), proton exchange membrane-based electrolysis (PEM), and solid oxide electrolysis (SOE) processes. Among these processes, the highest CO2 emission comes from the PEM electrolysis process, accounting for 4.68 kg-CO2/kg-H2, while the AE process provides the minimum total CO2 emissions of 3.28 kg-CO2/kg-H2. A similar trend was observed in the particulate matter (PM) emissions, and the PM2.5 emissions were 1.36, 1.30, and 1.24 kg-PM2.5/kg-H2 for PEM, SOE, and AE processes, respectively. Moreover, the environmental impact parameters of the processes were assessed, and the lowest global warming potential (GWP) of 3.32 kgCO2-eq./kg-H2 was obtained for the AE process. Accordingly, these results demonstrated that energy production techniques may be completely environmentally sustainable by substituting fully sustainable resources for the energy sources employed in current H2 production methods.